Rare bird documentation form for Glaucous Gull at Lake Manawa, 1982 - Myers, Robert K.et al (1982)
Rare bird documentation form for a Glaucous Gull at Lake Manawa in Pottawattamie County, IA on March 19, 1982. Epson - sheet feed